Carbon Fluxes of Contrasting Degraded Peatland Pilot Sites During Early-stage Restoration: Ex-milled Bare Peat and Grazed Grassland Conversion - Anna T. Keightley; Christopher D. Field; Michael Longden; Simon J. M. Caporn (Environmental Management, 2026)
The recovery of degraded peatlands can make significant contributions to reducing greenhouse gas emissions and climate warming. This study examines restoration techniques on shallow ex-milled peatland and intensively grazed pasture on deeper peat, both subject to prior drainage. Carbon greenhouse gases (GHGs) were monitored for 3 years following restoration treatment. After drainage-blocking measures, the ex-milled peatland was ‘companion planted’ with Eriophorum species and Sphagnum . The carbon balance was highly dependent on plant age and condition, with a high CO 2 equivalent (CO 2 e) uptake when plants were vigorously growing (year 1: −22.4 ± 32.9 t CO 2 e ha −1 yr −1 ), and high emission when plants were mature and in various stages of senescence (year 2: 26.1 ± 26.4 and year 3: 16.4 ± 9.7 t CO 2 e ha −1 yr −1 ). Bare peat controls had a mean emission of 6.21 ± 1.68 t CO 2 e ha −1 yr −1 over the study period. At the other site, the grazed pasture was stripped, the bare surface planted with Sphagnum plugs, and irrigation was intensively managed via bunding, ditches, and automatic water pumping. Carbon GHG emissions were significantly reduced on this ‘carbon farm’ (2.77 ± 0.95 t CO 2 e ha −1 yr −1 ) compared to a neighbouring drained, grazed pasture control (31.7 ± 10.3 t CO 2 e ha −1 yr −1 ) over the study period (mean ± SD throughout). It appears clear that the cyclical nature of Eriophorum plant growth may only deliver carbon benefits on shallow peat over the long term if groundwater levels can be adequately supported and if climatic conditions are favourable. Conversion of grazed pasture to wetter farming crops, such as Sphagnum , can potentially deliver immediate carbon benefits, although, in this pilot, any potential loss of CO 2 e due to degraded topsoil removal, creation of bunds and irrigation ditches was not accounted for.

Deep-time history of primate behavior and ecology as revealed by ancestral state reconstructions - Jeffrey K. Spear; Eva A. Hoffman; Juri A. Miyamae; Christopher D. Whalen; Alyssa M. Arre; Chloe Chen-Kraus; Margaret K. Corley; Matteo Fabbri; Jacques A. Gauthier; Michael Hanson; Amanda Leiss; Nicolás Mongiardino Koch; et al. (Journal of Mammalian Evolution, 2025)

Enhancing the review process in global environmental assessments: The case of the IPCC - Jean P. Palutikof; Sarah L. Boulter; Christopher B. Field; Katharine J. Mach; Martin R. Manning; Michael D. Mastrandrea; Leo Meyer; Jan C. Minx; Joy J. Pereira; Gian-Kasper Plattner; Suzana Kahn Ribeiro; Youba Sokona; et al. (Environmental Science & Policy, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

High uncertainty over the future of tidal marsh birds under current sea-level rise projections - Brian T. Klingbeil; Jonathan B. Cohen; Maureen D. Correll; Christopher R. Field; Thomas P. Hodgman; Adrienne I. Kovach; Erika E. Lentz; Brian J. Olsen; W. Gregory Shriver; Whitney A. Wiest; Chris S. Elphick (Biodiversity and Conservation, 2021)

Terrestrial gross primary production: Using NIR V to scale from site to globe - Grayson Badgley; Leander D. L. Anderegg; Joseph A. Berry; Christopher B. Field (Global Change Biology, 2019)
Terrestrial photosynthesis is the largest and one of the most uncertain fluxes in the global carbon cycle. We find that near‐infrared reflectance of vegetation (NIR V ), a remotely sensed measure of canopy structure, accurately predicts photosynthesis at FLUXNET validation sites at monthly to annual timescales ( R 2 = 0.68), without the need for difficult to acquire information about environmental factors that constrain photosynthesis at short timescales. Scaling the relationship between gross primary production (GPP) and NIR V from FLUXNET eddy covariance sites, we estimate global annual terrestrial photosynthesis to be 147 Pg C/year (95% credible interval 131–163 Pg C/year), which falls between bottom‐up GPP estimates and the top‐down global constraint on GPP from oxygen isotopes. NIR V ‐derived estimates of GPP are systematically higher than existing bottom‐up estimates, especially throughout the midlatitudes. Progress in improving estimated GPP from NIR V can come from improved cloud screening in satellite data and increased resolution of vegetation characteristics, especially details about plant photosynthetic pathway.

Understanding and responding to danger from climate change: the role of key risks in the IPCC AR5 - Katharine J. Mach; Michael D. Mastrandrea; T. Eren Bilir; Christopher B. Field (Climatic Change, 2016)

Contemporary evolution of resistance at the major insecticide target site gene Ace‐1 by mutation and copy number variation in the malaria mosquito Anopheles gambiae - David Weetman; Sara N. Mitchell; Craig S. Wilding; Daniel P. Birks; Alexander E. Yawson; John Essandoh; Henry D. Mawejje; Luc S. Djogbenou; Keith Steen; Emily J. Rippon; Christopher S. Clarkson; Stuart G. Field; et al. (Molecular Ecology, 2015)
Functionally constrained genes are ideal insecticide targets because disruption is often fatal, and resistance mutations are typically costly. Synaptic acetylcholinesterase ( AC hE) is an essential neurotransmission enzyme targeted by insecticides used increasingly in malaria control. In Anopheles and Culex mosquitoes, a glycine–serine substitution at codon 119 of the Ace‐1 gene confers both resistance and fitness costs, especially for 119S/S homozygotes. G119S in Anopheles gambiae from Accra (Ghana) is strongly associated with resistance, and, despite expectations of cost, resistant 119S alleles are increasing significantly in frequency. Sequencing of Accra females detected only a single Ace‐1 119S haplotype, whereas 119G diversity was high overall but very low at non‐synonymous sites, evidence of strong purifying selection driven by functional constraint. Flanking microsatellites showed reduced diversity, elevated linkage disequilibrium and high differentiation of 119S, relative to 119G homozygotes across up to two megabases of the genome. Yet these signals of selection were inconsistent and sometimes weak tens of kilobases from Ace‐1 . This unexpected finding is attributable to apparently ubiquitous amplification of 119S alleles as part of a large copy number variant ( CNV ) far exceeding the size of the Ace‐1 gene, whereas 119G alleles were unduplicated. Ace‐1 CNV was detectable in archived samples collected when the 119S allele was rare in Ghana. Multicopy amplification of resistant alleles has not been observed previously and is likely to underpin the recent increase in 119S frequency. The large CNV compromised localization of the strong selective sweep around Ace‐1 , emphasizing the need to integrate CNV analysis into genome scans for selection.

Heather Moorland Vegetation and Air Pollution: A Comparison and Synthesis of Three National Gradient Studies - Richard J. Payne; Simon J. M. Caporn; Christopher D. Field; Jacky A. Carroll; Jill L. Edmondson; Andrea Britton; Nancy B. Dise (Water, Air, & Soil Pollution, 2014)

Loss of whole-tree hydraulic conductance during severe drought and multi-year forest die-off - William R. L. Anderegg; Leander D. L. Anderegg; Joseph A. Berry; Christopher B. Field (Oecologia, 2014)

Drought's legacy: multiyear hydraulic deterioration underlies widespread aspen forest die‐off and portends increased future risk - William R. L. Anderegg; Lenka Plavcová; Leander D. L. Anderegg; Uwe G. Hacke; Joseph A. Berry; Christopher B. Field (Global Change Biology, 2013)
Forest mortality constitutes a major uncertainty in projections of climate impacts on terrestrial ecosystems and carbon‐cycle feedbacks. Recent drought‐induced, widespread forest die‐offs highlight that climate change could accelerate forest mortality with its diverse and potentially severe consequences for the global carbon cycle, ecosystem services, and biodiversity. How trees die during drought over multiple years remains largely unknown and precludes mechanistic modeling and prediction of forest die‐off with climate change. Here, we examine the physiological basis of a recent multiyear widespread die‐off of trembling aspen ( P opulus tremuloides ) across much of western N orth A merica. Using observations from both native trees while they are dying and a rainfall exclusion experiment on mature trees, we measure hydraulic performance over multiple seasons and years and assess pathways of accumulated hydraulic damage. We test whether accumulated hydraulic damage can predict the probability of tree survival over 2 years. We find that hydraulic damage persisted and increased in dying trees over multiple years and exhibited few signs of repair. This accumulated hydraulic deterioration is largely mediated by increased vulnerability to cavitation, a process known as cavitation fatigue. Furthermore, this hydraulic damage predicts the probability of interyear stem mortality. Contrary to the expectation that surviving trees have weathered severe drought, the hydraulic deterioration demonstrated here reveals that surviving regions of these forests are actually more vulnerable to future droughts due to accumulated xylem damage. As the most widespread tree species in N orth A merica, increasing vulnerability to drought in these forests has important ramifications for ecosystem stability, biodiversity, and ecosystem carbon balance. Our results provide a foundation for incorporating accumulated drought impacts into climate–vegetation models. Finally, our findings highlight the critical role of drought stress accumulation and repair of stress‐induced damage for avoiding plant mortality, presenting a dynamic and contingent framework for drought impacts on forest ecosystems.

The IPCC AR5 guidance note on consistent treatment of uncertainties: a common approach across the working groups - Michael D. Mastrandrea; Katharine J. Mach; Gian-Kasper Plattner; Ottmar Edenhofer; Thomas F. Stocker; Christopher B. Field; Kristie L. Ebi; Patrick R. Matschoss (Climatic Change, 2011)

Baseline Ecological Risk Assessment of the Calcasieu Estuary, Louisiana: Part 2. An Evaluation of the Predictive Ability of Effects-Based Sediment-Quality Guidelines - Donald D. MacDonald; Christopher G. Ingersoll; Dawn E. Smorong; Jesse A. Sinclair; Rebekka Lindskoog; Ning Wang; Corrine Severn; Ron Gouguet; John Meyer; Jay Field (Archives of Environmental Contamination and Toxicology, 2011)

Baseline Ecological Risk Assessment of the Calcasieu Estuary, Louisiana: Part 3. An Evaluation of the Risks to Benthic Invertebrates Associated With Exposure to Contaminated Sediments - Donald D. MacDonald; Christopher G. Ingersoll; Nile E. Kemble; Dawn E. Smorong; Jesse A. Sinclair; Rebekka Lindskoog; Gary Gaston; Denise Sanger; R. Scott Carr; James Biedenbach; Ron Gouguet; John Kern; et al. (Archives of Environmental Contamination and Toxicology, 2011)

Hydrogen peroxide‐induced oxidative stress responses in Desulfovibrio vulgaris Hildenborough - Aifen Zhou; Zhili He; Alyssa M. Redding‐Johanson; Aindrila Mukhopadhyay; Christopher L. Hemme; Marcin P. Joachimiak; Feng Luo; Ye Deng; Kelly S. Bender; Qiang He; Jay D. Keasling; David A. Stahl; et al. (Environmental Microbiology, 2010)
Summary To understand how sulphate‐reducing bacteria respond to oxidative stresses, the responses of Desulfovibrio vulgaris Hildenborough to H 2 O 2 ‐induced stresses were investigated with transcriptomic, proteomic and genetic approaches. H 2 O 2 and induced chemical species (e.g. polysulfide, ROS) and redox potential shift increased the expressions of the genes involved in detoxification, thioredoxin‐dependent reduction system, protein and DNA repair, and decreased those involved in sulfate reduction, lactate oxidation and protein synthesis. A gene coexpression network analysis revealed complicated network interactions among differentially expressed genes, and suggested possible importance of several hypothetical genes in H 2 O 2 stress. Also, most of the genes in PerR and Fur regulons were highly induced, and the abundance of a Fur regulon protein increased. Mutant analysis suggested that PerR and Fur are functionally overlapped in response to stresses induced by H 2 O 2 and reaction products, and the upregulation of thioredoxin‐dependent reduction genes was independent of PerR or Fur. It appears that induction of those stress response genes could contribute to the increased resistance of deletion mutants to H 2 O 2 ‐induced stresses. In addition, a conceptual cellular model of D. vulgaris responses to H 2 O 2 stress was constructed to illustrate that this bacterium may employ a complicated molecular mechanism to defend against the H 2 O 2 ‐induced stresses.

Interactive effects of elevated CO 2 , N deposition and climate change on extracellular enzyme activity and soil density fractionation in a California annual grassland - Hugh A. L. Henry; John D. Juarez; Christopher B. Field; Peter M. Vitousek (Global Change Biology, 2005)
Elevated CO 2 , N deposition and climate change can alter ecosystem‐level nutrient cycling both directly and indirectly. We explored the interactive effects of these environmental changes on extracellular enzyme activity and organic matter fractionation in soils of a California annual grassland. The activities of hydrolases (polysaccharide‐degrading enzymes and phosphatase) increased significantly in response to nitrate addition, which coincided with an increase in soluble C concentrations under ambient CO 2 . Water addition and elevated CO 2 had negative but nonadditive effects on the activities of these enzymes. In contrast, water addition resulted in an increase in the activities of lignin‐degrading enzymes (phenol oxidase and peroxidase), and a decrease in the free light fraction (FLF) of soil organic matter. Independent of treatment effects, lignin content in the FLF was negatively correlated with the quantity of FLF across all samples. Lignin concentrations were lower in the aggregate‐occluded light fraction (OLF) than the FLF, and there was no correlation between percent lignin and OLF quantity, which was consistent with the protection of soil organic matter in aggregates. Elevated CO 2 decreased the quantity of OLF and increased the OLF lignin concentration, however, which is consistent with increased degradation resulting from increased turnover of soil aggregates. Overall, these results suggest that the effects of N addition on hydrolase activity are offset by the interactive effects of water addition and elevated CO 2 , whereas water and elevated CO 2 may cause an increase in the breakdown of soil organic matter as a result of their effects on lignin‐degrading enzymes and soil aggregation, respectively.